2019
DOI: 10.1111/nmo.13587
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin for the treatment of hypercontractile esophagus: Results of a double‐blind randomized sham‐controlled study

Abstract: Introduction Botulinum toxin injection is known to be efficient to treat achalasia. We conducted a randomized trial in order to evaluate its efficacy to treat symptomatic hypercontractile esophageal disorders as characterized by esophageal high‐resolution manometry. Methods Patients with significant dysphagia and/or thoracic pain related to an hypercontractile esophageal motility disorder as defined by the Chicago Classification were randomized to receive an injection of botulinum toxin (100 U in 10 points in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
0
21
2
Order By: Relevance
“…However, a recent randomized study in patients with hypercontractile esophagus, including JE, demonstrated that symptom improvement after botulinum toxin was not superior to a sham procedure and that symptoms and manometric patterns may improve spontaneously over time 26 . Surprisingly, in this study, 3 out of 10 patients who did not receive any treatment had a favorable evolution of hypercontractile esophagus, including one with JE 26 ; this could be due to a placebo effect or to the spontaneous evolution of the disease. Regarding POEM, two recent multicenter retrospective studies demonstrated the efficacy of this technique in patients with a spastic motor disorder of the esophagus, including patients with JE, refractory to medical treatment, 13,15 and a recent meta‐analysis also confirmed these results 14 .…”
Section: Discussioncontrasting
confidence: 64%
“…However, a recent randomized study in patients with hypercontractile esophagus, including JE, demonstrated that symptom improvement after botulinum toxin was not superior to a sham procedure and that symptoms and manometric patterns may improve spontaneously over time 26 . Surprisingly, in this study, 3 out of 10 patients who did not receive any treatment had a favorable evolution of hypercontractile esophagus, including one with JE 26 ; this could be due to a placebo effect or to the spontaneous evolution of the disease. Regarding POEM, two recent multicenter retrospective studies demonstrated the efficacy of this technique in patients with a spastic motor disorder of the esophagus, including patients with JE, refractory to medical treatment, 13,15 and a recent meta‐analysis also confirmed these results 14 .…”
Section: Discussioncontrasting
confidence: 64%
“…Two RCTs compared endoscopic botulinum toxin injections in the esophagus with sham injections. The first study showed some effect of botulinum toxin on symptoms over and above that of the sham injection, but a second study showed no more effect for botulinum toxin than for the sham injection, with a benign natural history reported in both cohorts [70,71]. It thus seems questionable whether an invasive treatment such as POEM is justified in patients with spastic motility disorders, given this benign natural history and lack of evidence on efficacy and safety from methodologically sound studies.…”
Section: Poem For Spastic Esophageal Motility Disorders Other Than Acmentioning
confidence: 99%
“…The importance of a sham-or placebo-controlled study design is underlined by the results of a randomized sham-controlled botulinum toxin injection trial carried out by Mion et al32 In this study that included 23 patients with HE, there was no difference in symptom improvement, as assessed by the Eckardt score at 3 months, between patients who received Botox and those who were in the sham-control group. Patients in both groups reported symptom improvement, suggesting a relevant placebo effect in both treatment groups 32.…”
mentioning
confidence: 92%
“…The importance of a sham-or placebo-controlled study design is underlined by the results of a randomized sham-controlled botulinum toxin injection trial carried out by Mion et al32 In this study that included 23 patients with HE, there was no difference in symptom improvement, as assessed by the Eckardt score at 3 months, between patients who received Botox and those who were in the sham-control group. Patients in both groups reported symptom improvement, suggesting a relevant placebo effect in both treatment groups 32. A third paper published in this issue of the journal describes a patient in whom dysphagia and manometric signs of HE resolved immediately after radiofrequency ablation for atrial fibrillation33 The authors speculate that damage to extrinsic nervous fibers (vagus nerve branches?)…”
mentioning
confidence: 92%